Length-weight relationship and condition factor of three small indigenous fish species (Channa punctatus, Pethia ticto and Trichogaster fasciata) from the Turag river, Bangladesh (Bangladesh Journal of Zoology, 2025)
Length-weight relationship (LWR) and condition factor (K) are fundamental tools to evaluate the growth of a fish population and the health of the aquatic habitat. The present study was undertaken to investigate the length-weight relationship and condition factor of three small indigenous fish species namely, Channa punctatus, Pethia ticto, and Trichogaster fasciata from the Turag River, Bangladesh. The fish samples were collected from three different sites (Aichi, Arichpur and Rajabari) during the month of December 2022 to February 2023. A total of 63 fish samples of different sizes were collected for analysis. The total length of these fishes ranged between 6.0 to 18.2 mm, 4.1 to 8.0 mm, 6.8 to 9.5 mm with mean length of 10.62 mm, 6.42 mm, 8.12 mm and their weight ranged from 4 to 171g, 5 to 36g, 31 to 69g with mean weight of 41.48g,17.45g, and 52.8g for Channa, Pethia and Colisa spp. respectively. The study found that the values of the growth coefficient (b) for the 3 species varied greatly (P < 0.005) from 3 and ranged from 2.19 (Channa punctatus) to 2.82 (Pethia ticto) indicating negative allometric growth pattern in all species under this natural habitat. R2 value was calculated as 0.392, 0.852 and 0.944 for C. punctatus, P. ticto and Trichogaster fasciatarespectively. The value of Fulton’s condition factor (K) was lower than 1.0 reflecting the poor condition of the aquatic habitat to maintain the well-being of the fish species. This finding will provide insights towards sustainable stock management of the studied fish species in the Turag River, Bangladesh.Bangladesh J. Zool. 52(3): 237-245, 2024